O corpo singular como dispositivo de comunicação: uma leitura biopolítica da metodologia de Eugenio Barba - Santos, Ariane Alves dos (2015)
The research analyzes the notion of pre-expressiveness of the body, prepared by the theater director and researcher Eugenio Barba, proposing recognize it as a communicative device that explicitly and triggers the singularities of the body. This research part of trying to move its arts under the methodology for communication (corpomidia theory) and biopolitics. Thus, rather than a crosscultural theater actors to training, systematic proposed by Beard becomes a breeding device for testing new body communication processes, significantly increasing its importance as regards the life policy and their resistance networks. The corpus of the survey consists of his books The Secret Art of the actor: a theatrical anthropology dictionary and the paper canoe: treaty theatrical anthropology. These works are analyzed from authors such as Gilles Deleuze and Maurizio Lazzarato, to deepen the notion of uniqueness and individuation process; and Katz and Greiner to clarify the procedural aspects of the relationship between body and environment and culture as cognitive network. As a result, the dissertation proposes a different reading Beard methodology, interpreting it as a good example of what a communications professor Muniz Sodre has identified as sensitive communication strategies, not restricted to discursive practices and coded messages a priori